The Effect of Current Ratio and Total Assets Turnover on Return on Assets at PT Merck Indonesia Tbk for the Period of 2016-2023 - Muchamad Fahrul Fauji (International Journal of Scientific Multidisciplinary Research, 2024)
For the years 2016–2023, this study set out to analyse PT MERCK Tbk's Return On Assets (ROA) and how the Current Ratio and Total Asset Turnover impacted it. A descriptive associative technique is used in the study procedure, which is quantitative in nature. Secondary data extracted from PT MERCK Tbk's financial filings constitute the study's population. The quarterly financial statements of PT MERCK Tbk from 2016 to 2023 were used as the basis for the sample selection process, which used non-probability sampling using purposive sampling techniques. Multiple linear regression, t-tests, F-tests, coefficients of determination, and Pearson product-moment correlation analyses were used to assess the impact analysis. While the Total Asset Turnover (TATO) did not have any partial effect on Return On Assets (ROA), the Current Ratio did, according to the studies performed in this research. When used in conjunction, the Current Ratio and Total Asset Turnover (TATO) do not affect Return on Assets (ROA)